2020
DOI: 10.1029/2019jd031738
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitivity Study of Arctic Air‐Mass Transformation Using Large Eddy Simulation

Abstract: Arctic air mass transformation is linked to the evolution of low‐level mixed‐phase clouds. These clouds can alter the structure of the boundary layer and modify the surface energy budget. In this study, we use three‐dimensional large eddy simulation and a bulk sea ice model to examine the lifecycle of clouds formed during wintertime advection of moist and warm air over sea ice, following a Lagrangian perspective. We investigate the stages of cloud formation, evolution, and decay. The results show that radiativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…A8b and c). The influence of Aitken mode particles on ice is, in general, larger in MIMICA than in RAMS, which is consistent with the stronger cloud top cooling rates simulated by MIMICA that favours the ice formation through immersion freezing and growth by vapour deposition when the number of CCN increases (Possner et al, 2017;Solomon et al, 2018;Eirund et al, 2019).…”
Section: Influence Of Aitken Mode Aerosol Number Concentration On Closupporting
confidence: 78%
See 1 more Smart Citation
“…A8b and c). The influence of Aitken mode particles on ice is, in general, larger in MIMICA than in RAMS, which is consistent with the stronger cloud top cooling rates simulated by MIMICA that favours the ice formation through immersion freezing and growth by vapour deposition when the number of CCN increases (Possner et al, 2017;Solomon et al, 2018;Eirund et al, 2019).…”
Section: Influence Of Aitken Mode Aerosol Number Concentration On Closupporting
confidence: 78%
“…Maintenance of this layer is critical for sustaining longwave emission and ensuring cooling at the cloud top (e.g. Persson et al, 2017;Dimitrelos et al, 2020), which enhances a buoyancy-driven turbulent mixing in a layer within I. Bulatovic et al: The importance of Aitken mode aerosol particles -a simulation study and below the cloud (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The fourth International Polar Year (IPY, 2008) -a collaborative, international effort with intensive foci in the polar regionsinvolved several aircraft campaigns to characterize regional and transported aerosols and their impacts on clouds in the spring and summer in the North American Arctic Lathem et al, 2013;McFarquhar et al, 2011;Wang et al, 2011;Zamora et al, 2016), European Arctic (Ancellet et al, 2014), and Greenland (Quennehen et al, 2011;Thomas et al, 2013). More recent spring and summertime aircraft campaigns in the North American (Creamean et al, 2018c;Maahn et al, 2017), European (Eirund et al, 2019;Liu et al, 2015;Wendisch et al, 2019;Young et al, 2017;Young et al, 2016a, b), and Canadian Arctic sectors (Abbatt et al, 2019;Burkart et al, 2017;Schulz et al, 2019;Willis et al, 2019) involved a more comprehen-sive set of observations to assess spatiotemporal distributions of aerosols, their sources, and their impacts on cloud microphysics. While such Arctic airborne missions have yielded crucial information on aerosol sources and their impacts on clouds over the course of the last 3 decades, they are logistically and financially demanding, focus on relatively short and intensive periods, and can be affected by fast-flying flowinduced issues (Spanu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This is in part due to the unique behavior of AMPCs, which can persist for days within 1 km of the ground (Gierens et al, 2020;Morrison et al, 2012;Shupe, 2011;Shupe et al, 2011) and have been shown to increase surface temperature by almost 20 • C (Dimitrelos et al, 2020). Additionally, persistent Arctic mixed-phase stratocumulus clouds, which typically have low liquid water amounts, are particularly sensitive to modulations from aerosols compared to thicker stratocumulus clouds at other latitudes (de Boer et al, 2013;Eirund et al, 2019;Morrison et al, 2008;Norgren et al, 2018;. Therefore, both near-surface profiling and ground-based measurements equate to an ideal combination for investigating relationships between aerosols, clouds, and atmospheric state to address these issues and improve representation of aerosol impacts on Arctic cloud microphysics and radiative properties.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainties in model representations of aerosol-cloud interactions, especially in the Arctic, are exacerbated when models attempt to simulate cloud-radiative interactions and the surface energy budget (Sedlar et al, 2020). This is in part due to the unique behaviour of AMPCs, which can persist for days within 1 km of the ground (Gierens et al, 2020;Morrison et al, 2012;Shupe, 2011;Shupe et al, 2011) and have been shown to increase surface temperature by almost 20 ˚C (Dimitrelos et al, 2020). Additionally, Arctic clouds are particularly sensitive to modulations from aerosols (de Boer et al, 2013;Eirund et al, 2019;Morrison et al, 2008;Norgren et al, 2018;Solomon et al, 2018).…”
mentioning
confidence: 99%